Taxonomía y distribución de Vampyriscus brocki Peterson, 1968 (Phyllostomidae: Chiroptera) en Perú y primer registro para Ucayali - Ruelas Pacheco, Dennisse Cinthya; Pacheco, Victor (THERYA, 2015)
Introduction: The bat genus Vampyriscus Thomas, 1990 (Phyllostomidae) comprises V. bidens, V. brocki, and V. nymphaea, all occurring in the Neotropics, but only the first two are in Peru. We review the taxonomy and distribution of V. brocki in Peru, provide a new record, and compare with other similar species. Methods: Taxonomy and distribution of Vampyriscus brocki were reviewed based on voucher specimens and literature, morphologically compared with similar species, Vampyressa thyone and Vampyriscus bidens, and statistically analyzed with ANOVA (Î± = 0.05) and PCA. Results: Distribution of V. brocki comprises four departments in Peru from 120 to 1,000 m, including the first report presented here for Ucayali. Discrete and discriminating characters between V. brocki, V. bidens and Vampyressa thyone are provided, which is significantly supported by ANOVA (Î± = 0.05), and PCA. Discussion: Vampyriscus brocki from Peru are smaller than the specimens from French Guyana, suggesting the existence of interspecific variation. Presence of V. brocki is considered rare, migration and specialization for canopy are discussed as possible explanations. A biased sexual ratio in capture is found, with the females more represented than males. The sexual â€œdisproportionâ€ is probably because females fall more in the mist nets to explore more resources in more rainforest layers. The species has not yet been assessed by the IUCN Red List; we suggest it should be considered as Data Deficient.